2012
DOI: 10.3389/fonc.2012.00181
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of Robotic Stereotactic Body Radiosurgery for Metastatic Gynecologic Malignancies

Abstract: Background: Recurrent gynecologic cancers are often difficult to manage without significant morbidity. We conducted a phase II study to assess the safety and the efficacy of ablative robotic stereotactic body radiosurgery (SBRT) in women with metastatic gynecologic cancers. Methods: A total of 50 patients with recurrent gynecologic cancer who had single or multiple (≤4) metastases underwent robotic-armed Cyberknife SBRT (24Gy/3 daily doses). Toxicities were graded prospectively by common toxicity criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 24 publications
(43 reference statements)
8
73
0
1
Order By: Relevance
“…The selfreported incidence of pulmonary or chest-organ toxicity was very low in the 30-day period posttherapy. Reversible grade 2 or higher fatigue symptoms (20%) were in line with other SBRT trials (16%, [3]). Fatigue in the SBRT setting was attributed both to intense volumedirected radiation and to radiation-induced nuclear and mitochondrial DNA damage demanding excessive deoxynucleotide triphosphates, as considered before [20].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The selfreported incidence of pulmonary or chest-organ toxicity was very low in the 30-day period posttherapy. Reversible grade 2 or higher fatigue symptoms (20%) were in line with other SBRT trials (16%, [3]). Fatigue in the SBRT setting was attributed both to intense volumedirected radiation and to radiation-induced nuclear and mitochondrial DNA damage demanding excessive deoxynucleotide triphosphates, as considered before [20].…”
Section: Discussionsupporting
confidence: 73%
“…This notion was not new [1][2][3]. A prior observational study conducted in 27 patients suggested that a single 40% maximum standard uptake value benchmark sufficiently discriminated abdominopelvic SBRT clinical target volumes [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience has led investigators to use ablative radiation against a variety of tumor types metastasizing to the lung 27,28 . The new SBRT platform introduces a radiation delivery system particularly attuned to the treatment of moving tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For purposes of discussion here, the subclass of stereotactic radiosurgery dealing with robotics [Cyberknife®, Accuray (Sunnyvale, CA, USA)] will be the focus given the preponderance of clinical data accumulated worldwide [27][28][29][30]. Robotic cyberknife stereotactic body radiosurgery for gynecologic cancers most commonly involves ablative dose (>8 Gy) delivery [34,35], over a 30-60-min irradiation time span, with sub-millimeter precision [36,37] and with motion tracking [38] all in an effort to avoid injury to normal abdominopelvic tissues. Paramount to the integration of robotic stereotactic body radiosurgery in clinical radiation oncology practice is better understanding of natural systems of DNA damage repair.…”
Section: Rationale For Use In Gynecologic Malignanciesmentioning
confidence: 99%